Effect of acidified water on phenolic profile and antioxidant activity of dried blackcurrant (Ribes nigrum L.) pomace extracts - Ezzat Mohamad Azman (Tanjong Malim, 2022)
Effect of acidified water on phenolic profile and antioxidant activity of dried blackcurrant (Ribes nigrum L.) pomace extracts by Ezzat Mohamad Azman